The effect of HIV on patients’ lives: a phenomenological qualitative study - Naif S. Alzahrani; Abdulaziz Mofdy Almarwani (International Journal of Qualitative Studies on Health & Well-Being)
Introduction Human immunodeficiency virus (HIV) infection poses a significant threat to the immune system, compromising the body’s ability to combat diseases and infections. The Ministry of Health in Saudi Arabia reported an HIV incidence rate of 3 cases per 10,000 individuals. This study aimed to gain insight into the lived experience of Saudi patients living with HIV. Methods Employing a qualitative phenomenological approach, this study conducted in-depth interviews with 16 HIV patients (10 men, 6 women) between January 2023 and May 2023. Results Thematic data analysis highlighted three overarching themes and four subthemes. “Fear of the Future” encompassed subthemes including the fear of infecting a family member, fear of marriage, fear of employment recruitment, and fear of scandals. “Hopelessness” reflected the profound emotional state experienced by patients. “Overcoming Adversity” captured the resilience and strength demonstrated by individuals facing the challenges of living with HIV. Conclusion Saudi patients diagnosed with HIV encounter numerous obstacles in their daily lives. The fear of the future, including concerns such as infecting family members, marriage prospects, employment opportunities, and potential social repercussions, significantly impacts their overall well-being. By understanding the lived experience of HIV patients in Saudi Arabia, healthcare providers and policymakers can better support and enhance the quality of life for this population.